EXPERIMENTAL STUDY WITH USING ANFIS TO EVALUATE THE PERFORMANCE OF A MODIFIED CLOSED WET COOLING TOWER - MAHDI, QASIM SALEH; JAFFAL, HAYDER MOHAMMAD (Journal of Duhok University, 2017)
The present study involves experimental and computational analysis to investigate the thermal performance of modified closed wet cooling tower in perspective of first and second law of thermodynamics (analysis of energy and exergy) according to Iraqi weather. The experimental study includes design, manufacture and testing prototype of a modified counter flow forced draft closed wet cooling tower. The modification based on addition packing to the conventional closed wet cooling tower. To assess the thermal performance of cooling towera progression of tests was done at various operational and conformational parameters.The theoretical study included developed six models by an Adaptive Neuro-Fuzzy Inference System to anticipating various execution parameters of the tower including the cooling range, tower approach, thermal efficiency, cooling capacity, evaporation losses and exergy destruction. After simulating, three dimensional surface viewers obtained for future behavior of the thermal performance of cooling tower involves interactions between all operational parameters. Comparison of the output values obtained using the Adaptive Neuro-Fuzzy Inference System model and those obtained experimentally for other cases not included in the training data, indicates high compatibility with maximum percentage error of (5%).